2012
DOI: 10.1097/01.pra.0000413275.09305.d5
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrists’ Emotional Reactions to Patient Suicidal Behavior

Abstract: Attempted and completed suicides have a significant impact on psychiatrists. The impact of an attempted suicide is usually less severe. The patterns of reaction differ between consultant and trainee psychiatrists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…[1][2][3] Adverse psychological outcomes include feelings of anger, sadness, anxiety, guilt, embar-rassment, helplessness, and symptoms of posttraumatic stress disorder. 1,2,[4][5][6][7][8][9][10][11][12][13] Effects on professional behaviors include the loss of self-confidence in professional judgment, having difficulty with decision making, hospitalizing patients more often to prevent further suicides, increased interest in suiciderelated issues, hypervigilance regarding patient suicide, and preoccupation with medico-legal concerns. [10][11][12][13][14] In order to cope with patient suicide, clinicians often request further training in recognizing signs and symptoms of suicide, seek clear professional guidelines regarding how to deal with suicide, and look for new ways to support the bereaved family.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Adverse psychological outcomes include feelings of anger, sadness, anxiety, guilt, embar-rassment, helplessness, and symptoms of posttraumatic stress disorder. 1,2,[4][5][6][7][8][9][10][11][12][13] Effects on professional behaviors include the loss of self-confidence in professional judgment, having difficulty with decision making, hospitalizing patients more often to prevent further suicides, increased interest in suiciderelated issues, hypervigilance regarding patient suicide, and preoccupation with medico-legal concerns. [10][11][12][13][14] In order to cope with patient suicide, clinicians often request further training in recognizing signs and symptoms of suicide, seek clear professional guidelines regarding how to deal with suicide, and look for new ways to support the bereaved family.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have documented clinicians' intense negative emotional responses (e.g., anxiety, guilt, anger, helplessness, and hopelessness) when working with suicidal patients (Birtchnell, ; Goldblatt, ; Hendin, Lipschitz, Maltsberger, Haas, & Wynecoop, ; Kleespies & Dettmer, ; Kleespies, Penk, & Forsyth, ; Modestin, ; Scocco, Toffol, Pilotto, & Pertile, ). In a series of studies further exploring this interaction, our group found moderate to strong associations between clinicians' emotional responses to high‐risk patients, specifically conflicting emotional responses, and patients' subsequent suicidal behavior (Hawes et al., ; Yaseen, Galynker, Cohen, & Briggs, ; Yaseen et al., ).…”
mentioning
confidence: 99%
“…; Scocco et al . ; Yaseen et al . ) and experience difficulty both in controlling and in sharing their emotions, which can lead to negative attitudes and effects (Vedana et al .…”
Section: Discussionmentioning
confidence: 99%